Effect of aqueous neem leaves extract in controlling fusarium wilt banana (Musa spp.) - Ung, Yi (2020)
Neem leaf extracts (NLE) have frequently been applied to inhibit plant diseases and for the development of bio-fertilizer that leading to the commercial exploitation of this tree in agriculture. However, previous studies had indicated contradictory outcomes when it was applied as antifungal disease treatment and as bio-fertilizer when applied through the soil for several crops, including banana. Therefore, the present investigation was undertaken (i) to assess the growth of Fusarium oxysporum f. sp. cubense (Foc) fungus using a suitable media for control of pH in-vitro condition and (ii) to examine the occurrence and severity of diseases caused by Foc on banana “Cavendish” treated with NLE at the optimum soil acidity in the glasshouse condition. In 1A in-vitro experiment, different NLE rate from 0 to 10 ml was added into 250 ml of potato dextrose agar (PDA) media to grow the Foc fungus the while in the 1B experiment, the Foc were growth in different pH level (5, 5.5 as control, 6 and 7) of PDA media under complete randomized design (CRD) experimental design. In 1A experiment, colony radial extension decreased while the percentage of inhibition of radial growth (PIRG, %) increased significantly with increasing NLE rate for 7 days after incubation (DAI). However, no significant difference of all parameters was recorded for both 8 ml (8:250) and 10 ml (10:250) of NLE. Besides that, both pH 5 and 7 of PDA media also had the same effective significant effect in all parameters than under any other pH of the PDA media in the 1B experiment. Due to the planting condition of banana plants and according to significant differences, in Experiment 2, the best level of 8 ml aqueous NLE per 250 ml media (or at the ratio of 8:250 or 4:125) from Experiment 1A was applied to Fusarium-inoculated Cavendish banana (Musa spp. AAA group cv. ‘Grand Nain’) under the best soil media pH condition (optimum pH 7) from Experiment 1B. The 40 ml Fusarium fungus solution with the population of 2.50 x 108 spores ml-1 was poured onto the soil. The solution of NLE treatment was applied after one month of Fusarium application. The treatments in Experiment 2 were arranged by randomized complete block design (RCBD). Banana plants associated fungus were detrimental significantly and showed wilting symptoms. Foc resulting in high disease severity (leaves and rhizome) and incident of Fusarium wilt (%). Moreover, it was observed that the application of extract improves significantly in plant height, pseudo-stem diameter, root size and distribution, plant biomass production as well as soil physiochemical properties and tend to resist Fusarium wilt diseases. Thus, the major finding of this study shows that the application of NLE solution promotes better growth of cavendish banana plants and tend to withstand Fusarium wilt infection under optimum pH 7 media. Based on the results, aqueous NLE (at the ratio of 4:125) was recommended to be applied in the field as a treatment to improve Cavendish banana growth and delay Fusarium diseases damage to plants under pH7 soil condition.